1972
DOI: 10.1126/science.175.4027.1239
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Generation of Natural Aerosols from Vegetation

Abstract: It is suggested that an alternative, or additional, source of the blue haze above heavily forested areas may be the generation of submicrometer-sized wax particles by the action of strong electrical fields at the tips of pine needles and other wax-covered plant surfaces. Exposure of pine needles to high potential gradients results in the production of airborne wax particles with diameters less than 0.6 micrometer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Particulate K in the atmosphere can be associated with dust, sea salt, and especially plantderived material (Crozat 1978;Gosz 1980;Lovett & Lindberg 1984). Particles can be formed on plant surfaces by degradation of leaf tissue or by migration of salts from the interior to the exterior of leaves (Lovett et al 1989;Reiners et al 1986;Schaefer & Reiners 1989), and removed from the leaf surface by wind or by electrostatic forces (Beauford et al 1977;Fish 1972). These aerosol particles can be transported by wind and deposited to the bulk deposition collectors in clearings within the forest.…”
Section: Computation Methodsmentioning
confidence: 98%
“…Particulate K in the atmosphere can be associated with dust, sea salt, and especially plantderived material (Crozat 1978;Gosz 1980;Lovett & Lindberg 1984). Particles can be formed on plant surfaces by degradation of leaf tissue or by migration of salts from the interior to the exterior of leaves (Lovett et al 1989;Reiners et al 1986;Schaefer & Reiners 1989), and removed from the leaf surface by wind or by electrostatic forces (Beauford et al 1977;Fish 1972). These aerosol particles can be transported by wind and deposited to the bulk deposition collectors in clearings within the forest.…”
Section: Computation Methodsmentioning
confidence: 98%
“…Rasmussen and Went [1965] measured biogenic compounds in the air and reported that their occurrence was dependent upon the density of nearby vegetation, the season of the year, and the amount of decay of decomposing matter. It was also suggested that submicrometer aerosol wax particles could be produced in heavily forested areas by strong electrical fields on wax-covered plant surfaces [Fish, 1972]. They reported that photochemical processes were responsible for the eventual formation of biogenic particles at least 0.2 #m in diameter.…”
Section: Introductionmentioning
confidence: 99%
“…K, P, S, Zn) in plants are present in the fluids circulating in the plants and can be released from the plant during transpiration (Nemeruyk, 1970). Fish (1972) suggested that haze observed over forests could be due to submicrometer particles from electrical generation of biogenic aerosol by leaves. Furthermore, decaying vegetation may produce aerosol particles (Schnell and Vali, 1973).…”
Section: Introductionmentioning
confidence: 99%